2019
DOI: 10.1093/jas/skz259
|View full text |Cite
|
Sign up to set email alerts
|

Excess dietary leucine in diets for growing pigs reduces growth performance, biological value of protein, protein retention, and serotonin synthesis1

Abstract: An experiment was conducted to test the hypothesis that excess dietary Leu affects metabolism of branched-chain amino acids (BCAA) in growing pigs. Forty barrows (initial body weight [BW]: 30.0 ± 2.7 kg) were housed individually in metabolism crates and allotted to 5 dietary treatments (8 replicates per treatment) in a randomized complete block design. The 5 diets were based on identical quantities of corn, soybean meal, wheat, and barley and designed to contain 100%, 150%, 200%, 250%, or 300% of the requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Ile and Leu, resulted in lower feed intake after the oral gavage which was more pronounced around 2 h after treatment, suggesting a stronger effect on satiety rather than satiation. High dietary levels of Leu and Ile showed a strong anorexigenic effect potentially mediated by CCK and GLP-1 in pigs ( Millet et al, 2015 ; Kwon et al, 2019 ; Tian et al, 2019a ; Müller et al, 2022 ). The activation of long-term satiety signals such as leptin and insulin have also been described associated to dietary BCAA in pigs ( Lynch et al, 2006 ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ile and Leu, resulted in lower feed intake after the oral gavage which was more pronounced around 2 h after treatment, suggesting a stronger effect on satiety rather than satiation. High dietary levels of Leu and Ile showed a strong anorexigenic effect potentially mediated by CCK and GLP-1 in pigs ( Millet et al, 2015 ; Kwon et al, 2019 ; Tian et al, 2019a ; Müller et al, 2022 ). The activation of long-term satiety signals such as leptin and insulin have also been described associated to dietary BCAA in pigs ( Lynch et al, 2006 ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…C5 including two metabolites, that is, isovalerylcarnitine and methylbutyrylcarnitine was the product of Leucine and Isoleucine catalyzed by branched-chain α-keto acid dehydrogenase (BCKDH) complex, which also catalyze Valine to Isobutyryl COA (C4) [40]. C5 is a diagnostic indicator of Isovaleric acidemia (IVA, OMIM 243500), which is caused by abnormal leucine metabolism owing to isovaleryl-CoA dehydrogenase (IVD) deficiency [41].…”
Section: Performance Of the Final Newborn Metabolic Model For Identifmentioning
confidence: 99%
“…However, gain efficiency during the first 8 wk was not different between the two dietary treatments. Recently, studies showed that adding corn coproducts to diets may lead to an imbalance of branched chain AA as a result of the high dietary Leu concentration, which can reduce feed intake and, ultimately, growth performance of pigs ( Cemin et al, 2019 ; Kwon et al, 2019 ; Yang et al, 2019 ). However, diets containing HP-DDG in the current study contained not only high Leu concentrations but also adequate levels of Ile and Val based on recommendations from Htoo et al (2017) and Wiltafsky et al (2010) .…”
Section: Resultsmentioning
confidence: 99%